Social Network Analysis for Detecting Indicators of Favouritism in the Appointment of Corporate Managers - Sales, Luis A. M.; Victor, Andre Ormastroni; Basso, Rafael; Rocha, João F. C.; Contursi, Bruno S. N.; Meirelles, Thiago Pereira (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2024)
Several factors influence the choice of managers within organizations: previous experience, individual competencies, leadership attitudes, among many others. However, a central issue in the culture of corporate meritocracy is ensuring that there is no personal favouritism in the appointment of leading positions. This paper proposes a social network analytical approach to systematically measure the level of influence of connections between individuals in the appointments of managers. Promising preliminary results were validated through a case study containing historical data on workforce movement from a Brazilian mixed economy company.